The Concept of Islamic Education Muhammad Abduh and its Implications on Islamic Education in Indonesia - Is wanto (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
The dichotomic view that emerges in people's lives has a negative impact on Islamic education in Indonesia. Islamic education in Indonesia began to experience retardation and disintegration due to this dichotomic view. In fact, in the womb of Indonesian Islamic education there are not yet born scholars who have a deep spiritual and intellectual commitment. Therefore, this study offers the concept of Islamic education Muhammad Abduh as a solution. This study aims to elaborate on Muhammad Abduh's Islamic education concept and show the implications of Muhammad Abduh's Islamic education concept on Islamic education in Indonesia. This study uses a qualitative approach to the type of literature study research. The data collection technique used is the documentation technique. The data that has been collected is then analyzed using content analysis. Researchers found that the concept of Muhammad Abduh's Islamic education was to educate the minds and souls of students. Implications of the concept of Muhammad Abduh's Islamic Education to Islamic Education in Indonesia, among others, should the purpose of education pay attention to human nature as a whole. Students should both men and women add scientific insights. Educators should have good intellectual and religious competence. Learning methods that are applied should develop aspects of reason and soul (knowledge transfer and value transfer). Islamic education in Indonesia should study the treasures of modern science and religious scholarship. Keywords: The Concept of Islamic Education, Muhammad Abduh, Islamic Education in Indonesia